A Brief Review of Efficacious Plants in the World: Tagetes (Marigold) - Zahara, Meutia; Arifin, Vera Nazhira; Hamama, Syarifah Farissi (Journal of Tropical Biodiversity and Biotechnology, 2024)
Tagetes is a genus consisting of several efficacious plant species known as marigold, which is native to Mexico and has  spread worldwide due to its ability to adapt to different soil conditions. This genus is very popular among gardeners because it’s easy to cultivate, adaptable, produces flowers all year round, has a free flowering habit, short duration, and the flower has an attractive color and shape. It has many flowers of varying colors such as red, orange, yellow, mixed red-orange or red-yellow, but the yellow and orange color are the most popular. The flowers contain many carotenoids, which act as antioxidants, anti-bacterial, anti-inflammatory, anti-carcinogen, nematicide, and cosmetics. The carotenoid can also cure fever, epileptic fits, astringent, scabies, liver complaints, stomachache, sore throat, and  can be used as a natural moisturizer, and natural mosquito repellent Besides its use as a medicinal plant, Tagetes is also used as ornamental plants and edible plants. This manuscript’s endeavour is to include some important investigations and studies about the general description, phytochemicals compounds and essential oils, medicinal uses, natural pesticides, and food and beverage uses of the marigolds.